Clinical outcomes of interim positron emission tomography-computed tomography scan-guided response-adaptive therapy in advanced Hodgkin's lymphoma: a tertiary cancer centre experience from South India - Narasimman, Vasanth Rooban; Bakthavachalam, Ramkumar; Gopal, Raja; M., Pandidurai; J., Atul; Sharma, Manish Kumar; Parai, Shaoni; Gnanasekaran, Sridevi (International Journal of Research in Medical Sciences, 2024)
Background: Hodgkin’s lymphoma (HL) is a highly curable malignancy, but some patients fail standard ABVD chemotherapy, requiring intensified treatment. Interim positron emission tomography-computed tomography scan (iPET-CT) using the Deauville scoring system allows response-adapted therapy, enabling de-escalation to AVD in good responders and escalation to dose-escalated BEACOPP (EB) in poor responders. This study evaluates iPET-guided therapy outcomes in HL patients at a tertiary care center in South India. Methods: A retrospective study of 69 HL patients (aged 12-65 years) treated over 5 years was conducted. After two ABVD cycles, iPET-2 scans guided treatment: PET-negative patients (Deauville 1-3) received four additional AVD cycles, while PET-positive patients (Deauville 4-5) received four EB cycles. The primary endpoint was event-free survival (EFS); secondary endpoints included overall survival (OS), toxicities, and quality of life. Statistical analyses included Kaplan-Meier survival analysis and Cox regression. Results: The cohort (median age: 38 years, 87% male) had predominantly advanced-stage disease (73.9%) and systemic B symptoms (81.2%). iPET identified 16% as PET-positive. Median OS was 73 months (95% CI: 67.77-78.23), and median EFS was 30 months (95% CI: 28.64-31.36). PET-negative patients showed significantly better 2-year EFS (81%) compared to PET-positive patients (50%; p<0.05). Toxicities were higher in the EB group, with grade 3-4 neutropenia in 85% of cycles. Conclusions: iPET-CT-guided therapy effectively stratifies HL patients, improving outcomes in PET-positive poor responders while avoiding overtreatment in PET-negative patients. Despite higher toxicities, escalated BEACOPP was feasible and safe, highlighting the potential of response-adapted strategies in resource-limited settings.